Blood flow suspension in tapered stenosed arteries for Walter's B fluid model. Issue 132 (August 2016) - Akbar, Noreen Sher
Highlights: Scrutiny of blood flow in tapered stenosed arteries for Walter's B fluid model. The MHD 2-dimenssional flow of blood fluid is present. Perturbation solutions are obtained for coupled ordinary differential equations. Graphical results are obtained for each physical parameter. First article in peristaltic literature to discuss this model. Abstract: Background and objectives: In the present article, I have studied the blood flow of a Walter's B fluid through a tapered artery with a stenosis. The problem is modeled in cylindrical coordinates system. Methods results conclusions: The analytical solutions have been carried out using regular perturbation method by taking α as perturbation parameter. The expressions for velocity, resistance impedance, wall shear stress and shearing stress at the stenosis throat have been evaluated. The graphical results of different types of tapered arteries (i.e. converging tapering, diverging tapering, non-tapered artery) have been examined for different parameters of interest.